The Effect of Physical Activity on Mood - Ayu Ria Azizah; Mohammad Zaky; Jajat (Journal of Physical Education Health and Sport, 2025)
Physical activity is considered to affect mood, but this relationship is not always consistent and may depend on the context of the activity and individual characteristics. This study aims to analyze the effect of physical activity on mood among members of a recreational sports community using a cross-sectional study design involving 52 respondents selected through purposive sampling. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ) and grouped into three type of activities (running, trail run, and cycling), while mood was measured using the Brunel Mood Scale (BRUMS). Data analysis was performed using One-Way ANOVA test, which showed that there were no significant differences in physical activity levels between activity groups (F = 2.502; p = 0.092) or in mood conditions between physical activity groups (F = 2.006; p = 0.145). These findings indicate that physical activity does not have a significant effect on mood in the recreational sports community in this study, suggesting taht the relationship between physical activity and mood is complex and may be influenced by other factors such as intensity, consistency, social context, and unmeasured psychological variables.